Reality Meets Belief: A Mixed Methods Study on Character Strengths and Well-Being of Hospital Physicians - Kachel, Timo; Huber, Alexandra; Strecker, Cornelia; Höge, Thomas; Höfer, Stefan (Frontiers in Psychology, 2021)
Positive psychology deals with factors that make life most worth living and focuses on enhancing individual potentials. Particularly, character strengths can positively contribute to well-being and work-related health, bearing a promising potential for professions, such as physicians, who are at risk for burnout or mental illnesses. This study aims to identify beneficial character strengths by examining the quantitative and qualitative data. In a cross-sectional multi-method study, 218 hospital physicians completed an online survey assessing their character strengths and their general and work-related well-being, comprising thriving, work engagement, and burnout dimensions (outcome variables). Quantitative data were analyzed for the total sample and by tertiary split. Additionally, interview-gathered opinions of four resident physicians and four medical specialist educators were collected to expand the perspective on which character strengths might be beneficial for the well-being of the resident physicians. The highest significant correlations between character strengths and outcome variables were found for hope and thriving (r = 0.67), zest, and work engagement (r = 0.67) as well as emotional exhaustion (r = −0.47), perseverance/leadership and depersonalization (r = −0.27), bravery, and reduced personal accomplishment (r = −0.39). Tertiary splits revealed that some correlations were not consistent across the entire scale continuum, for example, creativity was only significantly correlated with comparatively high levels of thriving (r = 0.28) or forgiveness with comparatively high levels of depersonalization (r = −0.34). Humility, social intelligence, and teamwork showed predominantly low correlations with all outcome variables (r = −0.17 − 0.34), although humility was stated by all interviewed medical specialist educators to be the most relevant for the well-being at work, and the latter two by three resident physicians, respectively. Different perspectives resulting from quantitative and qualitative data in terms of beneficial character strengths for work-related well-being may be driven by different work experiences, professional understandings, generational beliefs, or social expectations. Some significant correlations between character strengths and well-being outcomes varied depending on low, medium, or high outcomes. This raises questions about suitable work-related well-being interventions, as simple single intervention approaches (one intervention fits all) may not work for the respective outcome levels. These new findings warrant further research on how to foster the well-being of resident physicians at work.